Efeito de pausas ativas e passivas e da variação de ritmo de trabalho na atividade eletromiográfica e oxigenação de músculos escapulotorácicos em mulheres com e sem dor no pescoço-ombro durante a realização de uma tarefa manual repetitiva. - Januário, Letícia Bergamin (2018)
The main objective of this PhD thesis was to evaluate the effects of including active pauses and changing work pace on the neck-shoulder region of women during a repetitive simulated industrial task, considering the measurements of surface electromyography, muscle oxygenation and 2D kinematics. This research was based on four studies: (Study 1) the synthesis of the methods used to apply and analyze the active pauses during the performance of monotonous, repetitive and static tasks, through a systematic review; (Study 2) the investigation of the effects of active and passive pauses and the implementation of different work paces on the electromyographic activity (EMG) of trapezius and anterior serratus muscles during a repetitive task performed by women without musculoskeletal symptoms on the neck- shoulder region; (Study 3) the evaluation of the effects of active and passive pauses, on upper trapezius muscle oxygenation and upper body posture, considering a single work pace and comparing women with and without neck-shoulder pain; and finally (Study 4) the investigation of implementing different work paces on the functional connectivity from muscles of the scapulothoracic region during the performance of a repetitive task performed by women with and without musculoskeletal symptoms on the neck-shoulder region. The literature review included 15 studies and found that active pauses were partially able to change the EMG level during monotonous activities to a more beneficial pattern of muscle activity. However, the synthesis of evidence was limited and the results should be considered with caution. On the other studies (2-4), the experimental procedure used to evaluate the active pauses and the implementation of different work pace in an experimental setting was based on a standard, repetitive, monotonous and assembly-like task. We evaluated women with and without chronic pain in the neck-shoulder region in terms of EMG of acromial and clavicular portions of the upper trapezius, middle trapezius, lower trapezius and anterior serratus muscles; (b) upper trapezius muscle oxygenation; (c) posture of head, trunk and arm. The Study 2 pointed out that contrary to the hypothesis raised, no interaction between work pace and pause type was found. The slow pace resulted in an acute decrease in biomechanical exposure in terms of EMG and more variation in the activation pattern of scapulothoracic muscles when compared to the same task performed at fast pace. Considering the types of pauses applied, no significant difference was found between passive and active pauses, contrary to previous studies, except that the active pauses resulted in an increased EMG activation level in the clavicular portion of the upper trapezius. Study 3 reveled that active pauses are capable of promoting an increase in muscle oxygenation of the dominant upper trapezius and also modifying the postures of head, upper trunk and arm during a repetitive assembly task, but unlike hypothesized women with and without neck-shoulder pain had similar results in terms of oxygenation and postures of the upper body region. Study 4 revealed that contrary to our hypothesis, the groups with and without neck-shoulder pain had similar electromyographic patterns in terms of EMG amplitude, muscular rest level and functional connectivity. When comparing paces, it was possible to observe that the fast movement pace imposed a greater biomechanical load, evidenced by higher amplitude EMG, lower degree of muscular rest and higher level of functional connectivity in comparison to the slow pace. Generally, we can conclude that the proposed interventions did not interact between themselves and that no significant differences between women with and without neck-shoulder pain were found in terms of EMG, oxygenation and posture. The slow pace led to a higher variation and lower functional connectivity of the scapulothoracic muscles, which indicates a decrease on the biomechanical load of this region. The active pauses pointed out towards benefits in terms of muscle oxygenation and upper body posture, even though no significant differences were found in terms of EMG when compared with passive pauses.